Faktor-Faktor Yang Mempengaruhi Volatilitas Harga Saham pada Perusahaan LQ45 di Bursa Efek Indonesia - Ridho, Muhammad (Jurnal Rekoginisi Ekonomi Islam, 2024)
This research aims to find out: Effects of Profitability, Leverage, Inflation, Exchange Rates on Stock Price Volatility (Empirical Study of LQ45 Companies Registered on the IDX in 2018-2021) aims to examine and discuss the effect of Profitability, Leverage, Inflation, Exchange Rates on Volatility Stock price. This type of research is quantitative with secondary time series data. The This type of research is quantitative with secondary time series data. The population in this study are companies listed on the LQ 45 Index on the IDX for 2018-2021 in the company's annual report LQ 45 Index on the official website of the Indonesian Stock Exchange (IDX). The sampling technique uses a purposive sampling technique. The data analysis technique used is Multiple regression analysis techniques, descriptive statistics, hypothesis testing, and classical assumption testing. The results of this study are that the Profitability and Leverage variables have a significant negative effect on Stock Price Volatility, the Inflation variable has a significant positive effect on Stock Price Volatility, while the Exchange Rate variable has no significant effect on Stock Price Volatility.